Gender-Based Role Transformation in Contemporary Muslim Families: A Comparative Study of Indonesia, Egypt, and Iran - Mufid Arsyad; Habib Ismail; Linda Firdawaty (Jurnal Studi Gender dan Anak, 2025)
The transformation of gender roles in Muslim countries shows diverse dynamics due to the influence of religious interpretations, political systems, and social structures in each country. This study examines the transformation of gender roles in Muslim families in Indonesia, Egypt, and Iran through a descriptive-comparative approach. Data were collected from policy documents and relevant literature. The results show that the transformation of gender roles in Muslim families cannot be separated from the interaction between religion, state, and society. In Indonesia, cultural pluralism and an open legal system support women's involvement in the public sphere. In Egypt, change is hampered by conservative norms despite a strong feminist heritage. Meanwhile, in Iran, women face institutionalized restrictions but show resistance through social movements and education. This research emphasizes the importance of cross-border dialogue among Muslim countries in promoting contextual, equitable gender transformation that is in line with local values. [Transformasi peran berdasarkan gender di negara muslim menunjukkan dinamika yang beragam berbeda karena dipengaruhi oleh interpretasi agama, sistem politik, dan struktur sosial masing-masing negara. Penelitian ini mengkaji transformasi peran gender dalam keluarga Muslim di Indonesia, Mesir, dan Iran melalui pendekatan deskriptif-komparatif. Data dikumpulkan dari dokumen kebijakan dan literatur yang relevan. Hasil penelitian menunjukkan bahwa transformasi peran gender dalam keluarga Muslim tidak dapat dilepaskan dari interaksi antara agama, negara, dan masyarakat. Di Indonesia, pluralisme budaya dan sistem hukum yang terbuka mendukung keterlibatan perempuan di ranah publik. Di Mesir, perubahan terhambat oleh kekuatan norma konservatif meskipun ada warisan feminisme kuat. Sementara itu, di Iran, perempuan menghadapi pembatasan yang dilembagakan meski menunjukkan resistensi melalui gerakan sosial dan pendidikan. Penelitian ini menegaskan pentingnya dialog lintas negara Muslim dalam mendorong transformasi gender yang kontekstual, adil, dan sejalan dengan nilai-nilai lokal].